2014
DOI: 10.1126/scitranslmed.3008761
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Culture–Derived MF59-Adjuvanted Pandemic A/H7N9 Vaccine Is Immunogenic in Adults

Abstract: A potentially deadly A/H7N9 avian-origin influenza virus is currently the cause of an ongoing outbreak in China. Preparedness plans have thus been initiated to preempt the spread of this virus, which appears to have substantial pandemic potential. To effectively prevent a pandemic from unfolding, rapid production of an immunogenic vaccine with an acceptable safety profile is critical. Given the significance to public health, we are reporting immunogenicity and safety results from a phase 1 study in healthy adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 49 publications
7
64
0
Order By: Relevance
“…Accumulated evidence has demonstrated that A(H7N9) vaccines have poor immunogenicity without an adjuvant. Even at a higher dosage of 45 g of HA, only minimal antibody responses were induced (32), while the incorporation of an adjuvant, such as MF-59, and Iscomatrix in the A(H7N9) vaccine formation enhanced the immunogenicity significantly (30,31). Thus, the conventional vaccination regimen may not be adequate to elicit the optimal neutralization antibody response unless a higher antigen dose or adjuvant or immune potentiation measures are considered (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated evidence has demonstrated that A(H7N9) vaccines have poor immunogenicity without an adjuvant. Even at a higher dosage of 45 g of HA, only minimal antibody responses were induced (32), while the incorporation of an adjuvant, such as MF-59, and Iscomatrix in the A(H7N9) vaccine formation enhanced the immunogenicity significantly (30,31). Thus, the conventional vaccination regimen may not be adequate to elicit the optimal neutralization antibody response unless a higher antigen dose or adjuvant or immune potentiation measures are considered (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the development of A(H7N9) vaccines has encountered the problems of a low seroconversion rate and low titer of antibody response in animal models and several human clinical trials (28)(29)(30)(31). Accumulated evidence has demonstrated that A(H7N9) vaccines have poor immunogenicity without an adjuvant.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical development of influenza vaccines is ongoing, however split virus or subunit vaccines for avian influenza are known to be poorly immunogenic (26,27) and often require multiple doses and/or formulation with potent adjuvants to achieve seroconversion (28). Although live attenuated vaccines (LAIVs) can induce of both humoral and cellular immunogenicity, in adults these vaccines have previously been associated with lower seroconversion rates and higher rates of laboratory-confirmed influenza when compared to trivalent influenza vaccine.…”
Section: Prime-boost Vaccinated Mice Intranasally Challenged With DIVmentioning
confidence: 99%
“…20 The results of alternative vaccine strategies have also been subpar with both inactivated H7N9 split vaccine and H7N9 HA virus-like particle vaccine eliciting HI seroconversion rates of only 6% and 15.6% in Phase I trials respectively. 21,22 This compares poorly with the ~ 89% rate reported for similar seasonal influenza subunit vaccines. 2325 Even with the addition of adjuvant and a booster injection, the inactivated split H7N9 vaccine elicited HI seroconversion in only 59% of subjects in an early Phase II clinical trial.…”
Section: Challenges To Preparedness For An Avian H7n9 Influenza Pandemicmentioning
confidence: 59%